2001
DOI: 10.1046/j.1365-2613.2001.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and local effects of long-term exposure to alkaline drinking water in rats

Abstract: Alkaline conditions in the oral cavity may be caused by a variety of stimuli, including tobacco products, antacids, alkaline drinking water or bicarbonate toothpaste. The effects of alkaline pH on oral mucosa have not been systematically studied. To assess the systemic (organ) and local (oral mucosal) effects of alkalinity, drinking water supplemented with Ca(OH) 2 or NaOH, with pH 11.2 or 12 was administered to rats (n 36) for 52 weeks. Tissues were subjected to histopathological examination; oral mucosal bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…From a clinical perspective, SRW can be safely applied to the oral cavity. Merne et al [29] showed that the oral mucosae of rats allowed to drink alkaline water (pH, 11.2 and 12.0) for 52 weeks remained unaffected by the high alkalinity without any specific morphologic alterations. However, the application of calcium hydroxide paste, which has a pH almost similar to that of alkaline electrolyzed water, to the oral mucosa of rats and hamsters resulted in cell atypia [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical perspective, SRW can be safely applied to the oral cavity. Merne et al [29] showed that the oral mucosae of rats allowed to drink alkaline water (pH, 11.2 and 12.0) for 52 weeks remained unaffected by the high alkalinity without any specific morphologic alterations. However, the application of calcium hydroxide paste, which has a pH almost similar to that of alkaline electrolyzed water, to the oral mucosa of rats and hamsters resulted in cell atypia [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Low water pH will cause redness and irritation to eyes below a pH of 4. And while a water pH of 2.5 or lower is uncommon, exposure to water of this acidity will cause extensive and irreversible damage to the skin cells that detect sensation [14].…”
Section: Phmentioning
confidence: 99%
“…Symptoms of effect of drinking water with high Zinc includes: nausea, vomiting, dizziness, fevers, diarrhea and acute toxicity leading to stomach aches. Other related health effects also include mucous membrane infection [14,15,17].…”
Section: Zincmentioning
confidence: 99%
“…Specific information about drinking water source, delivery methods, and treatments (e.g., acidification, chlorination, sterilization) is important to provide; some treatments, in particular, are known to affect certain experimental parameters (Bjornsson et al 2003;Hall et al 1980;Hermann et al 1982;Merne et al 2001). In certain types of studies water delivery methods have been known to be an important component of husbandry as well (Gordon and Wyatt 2011).…”
Section: Watermentioning
confidence: 99%